Beschreibungen von simultan wahrnehmbaren Kunstwerken – zu einem spezifischen Typ deskriptiver Sprechhandlungen - Düring, Daniel (Linguistik Online, 2025)
Verbal/Written descriptions of artworks that are perceived whilst a person looks at an artwork can be seen as a specific type of the verbal action pattern to describe. My thesis in this article is that the action purpose is not simply to ‘create a picture’ in the hearer’s or reader’s imagination space, but to lead a successive acquisition and processing of knowledge with regard to relevant aspects of the artwork (as it is represented in the describer’s knowledge).Therefore, descriptions of this type prepare for mental and/or verbal forms of action (for example to explain, to evaluate). Based on action-theoretical works from the field of Functional Pragmatics the article presents analyses of texts and discourses on descriptions of artworks that can be perceived simultaneously. The following questions are taken into account:• In what ways are the describer’s verbal actions based on a shared knowledge space, respectively, a shared perception space?• Which forms of synchronizations with local deixis can be differentiated and are typical for this type of constellation?• Which interrelations between the describer’s concatenation of speech and the hearer’s/ reader’s successive viewing of the perception and acquisition of knowledge (respectively processing of knowledge) can be found?• Which linguistic forms are common with regard to the function to create an interactional nexus with other verbal action patterns (for example ‘to explain’)?